Doing Business in America A Jewish History - Diner, Hasia R. (Purdue University Press, 2018)
American and Jewish historians have long shied away from the topic of Jews and business. Avoidance patterns grew in part from old, often negative stereotypes that linked Jews with money, and the perceived ease and regularity with which they found success with money, condemning Jews for their desires for wealth and their proclivities for turning a profit. A new, dauntless generation of historians, however, realizes that Jewish business has had and continues to have a profound impact on American culture and development, and patterns of immigrant Jewish exploration of business opportunities reflect internal, communal, Jewish-cultural structures and their relationship to the larger non-Jewish world. As such, they see the subject rightly as a vital and underexplored area of study. Doing Business in America: A Jewish History, edited by Hasia R. Diner, rises to the challenge of taking on the long-unspoken taboo subject, comprising leading scholars and exploring an array of key topics in this important and growing area of research.